PERANCANGAN APLIKASI INFORMASI WARISAN BUDAYA MEGALITIK Studi Kasus: Pasemah Megalitik Sumatera - Santo Tjhin; Rahmadia Putri (Universitas Trisakti, 2021)
AbstractDesigning Megalithic Cultural Heritage Information Application (Case Study: Sumatran Megalithic Pasemah). Pasemah plateau is a historic plateau. There is a prehistoric heritage site that has a megalithic tradition because it has megalithic artifacts from the megalithic era. In 2012, Pasemah's megalithic cultural heritage was registered by the Government of Pagaralam as one of the world's heritages. Researchers designed the Pasemah megalithic cultural heritage application, which is an active effort to support the development of the megalithic cultural heritage in Pasemah through appropriate technological innovations. By utilizing internet technology in the form of applications can disseminate information quickly and reach the wider community. The method in designing the application uses the Design Thinking method. The design is more focused on strengthening the concept of the story